Legal Issues and Challenges in Securing Ugandans' Health Rights in Vaccine Safety - Paul Atagamen Aidonojie; Esther Chetachukwu Aidonojie; Hassan Adebowale Ismiala; Muwaffiq Jufri; Collins Ekpenisi (Legalis : Journal of Law Review, 2026)
Health is widely regarded as a form of wealth and a fundamental human right that governments must protect. In response to global infectious diseases, the international community has increasingly relied on vaccine development as a strategy to mitigate major health threats. However, public concerns such as those raised by Dr. Wahome Ngare’s medical team regarding the safety of certain vaccines highlight the urgent need for strong legal and institutional mechanisms to safeguard public health. Against this backdrop, the study examines Uganda’s legal framework for protecting citizens’ health rights and explores the structural challenges that may hinder the effectiveness of these laws. Using a doctrinal research method, the study draws on primary and secondary legal materials and analyzes them through descriptive and analytical approaches. The findings reveal that unsafe vaccines can pose severe risks to human health. The Ugandan government is legally obligated, under both international and domestic law, to ensure that vaccines circulating within the country are safe and effective. Despite this mandate, several obstacles limit the implementation of health protections, including constitutional barriers to the application of international law, bureaucratic delays in enforcing national regulations, resource constraints, and low public awareness of the health reporting system. The study concludes by reaffirming the need to strengthen the protection of Ugandans’ health rights. It recommends that the government address these challenges by domesticating reliable international legal standards, reducing internal legal bureaucracy, and improving public awareness of health reporting mechanisms. This research contributes to the broader understanding of how Uganda’s legal and institutional structures support public health rights, while identifying gaps, accountability issues, and policy challenges related to vaccine safety and public trust.